Data Mining Perbandingan Algoritma K-Nearest Neighbor dan Naïve Bayes dalam Prediksi Penerimaan Beasiswa - Ahmad Ilham Kushartanto; Rima Tamara Aldisa (Journal of Computer System and Informatics (JoSYC), 2023)
One of the goals of the Indonesian State as stated in the Constitution of the Republic of Indonesia is to make the nation's life more intelligent. The government, through the Ministry of Education, Culture, Research and Technology (Kemendikbudristek), is implementing a 12-year compulsory education program. The Indonesia Smart College Card program will start to be implemented in 2021, where initially this program was called bidikmisi. The Indonesia Smart College Card program is intended to help children who experience economic difficulties or are constrained by the costs of continuing their education at tertiary level. Beneficiaries of the Indonesian Smart College Card program will receive full tuition fees from the start of admission to completion of the course within the agreed time period. This aims to ensure that children who have been selected to become students no longer have to worry or feel afraid about their survival when studying. Placing limits on the number of recipients of the Indonesia Smart Tuition Card for Private Universities (PTS) is a problem that must be resolved properly and carefully. The selection process for prospective students who register at the target university aims to find recipients who are worthy of assistance from the Indonesia Smart College Card program. The selection process for prospective students who register at the target university aims to find recipients who are worthy of assistance from the Indonesia Smart College Card program. The results obtained from the application of the research were that from comparing the results of the K-NN and Naive Bayes algorithms, the same results were obtained for the test data, namely Acceptable.